HUBUNGAN PENGETAHUAN DAN USIA KEHAMILAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS TALANG RATU PALEMBANG TAHUN 2013 - Juliana Widyastuti Wahyuningsih Juliana Widyastuti Wahyuningsih (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2014)
ABSTRACT Based on data from the WHO estimates that 35% -75% of pregnant women in developing countries and 18% of pregnant women in developed countries suffer from anemia. According to the 2001 SKRT, the incidence of anemia in pregnant women is 40%, in women of childbearing age is 15-44 years old 27.9% and 48.1% are children under five. This study aims to determine the relationship of knowledge and gestational age with the incidence of anemia in pregnant women at the Puskesmas Talang Ratu Palembang 2013. This type of survey research is cross sectional analytic approach. The study population was all pregnant women during their pregnancy to the Puskesmas Talang Ratu Palembang on research time. Sampling was carried out research with nonprobability sampling technique Accidental Sampling. This study is the total sample population of pregnant women during their pregnancy to the Puskesmas Talang Ratu Palembang research amounted to 30 respondents. Time studies were conducted on May 7, 2013 until May 15. Instruments collecting data on the incidence of anemia is done by examination of Hb as measured using the Sahli hemoglobin and data on gestational age is done by fundus examination. Knowledge about the data collection instrument used was questionnaire as an interview guide. The variables studied were the dependent variable (incidence of anemia) and independent variables (knowledge and gestational age). The results showed that respondents with the incidence of anemia 7 respondents (23.3%) and respondents did not anemia is 23 respondents (76.7%). Respondents with high knowledge of the 11 respondents (36.7%) and respondents with low knowledge of the 19 respondents (63.3%). Respondents to the first trimester of pregnancy is 12 respondents (40%), respondents to the second trimester of gestation is eight respondents (26.7%) and respondents to the third trimester of pregnancy is 10 respondents (33.3%). The results of chi-square analysis (X2) between the dependent variable showed there is relationship with independent significant association between knowledge of the incidence of anemia, with a p value = 0021 <0.05, andthere is significant relationship between gestational age with the incidence of anemia, in which the p value = 0009 < 0.05, at the Puskesmas Talang Ratu Palembnag Palembang. Expected to be input for health personnel, especially midwives in health centers Gutter Queen Palembnag to providing information about the incidence of anemia. ABSTRAK Berdasarkan data dari WHO memperkirakan 35%-75% ibu hamil di negara berkembang dan 18% ibu hamil di negara maju mengalami anemia. Menurut SKRT tahun 2001, angka kejadian anemia pada ibu hamil adalah sebesar 40%. Penelitian ini bertujuan untuk mengetahui hubungan pengetahuan dan usia kehamilan dengan kejadian anemia pada ibu hamil di Puskesmas Talang Ratu Palembang Tahun 2013. Jenis penelitian ini survey analitik melalui pendekatan cross sectional. Populasi penelitian ini semua ibu hamil yang memeriksakan kehamilan ke Puskesmas Talang Ratu Palembang pada waktu penelitian. Pengambilan sampel pada penelitian ini dilakukan secara Nonprobability Sampling dengan teknik Accidental Sampling. Sampel penelitian adalah total populasi ibu hamil yang memeriksakan kehamilan ke Puskesmas Talang Ratu Palembang pada waktu penelitian berjumlah 30 responden. Waktu penelitian dilakukan tanggal 7 Mei sampai 15 Mei Tahun 2013. Instrumen pengumpulan data kejadian anemia dilakukan dengan pemeriksaan Hb yang diukur dengan menggunakan Hb Sahli dan data usia kehamilan dilakukan dengan cara pemeriksaan fundus uteri. Instrumen pengumpulan data pengetahuan yang digunakan adalah kuesioner sebagai panduan wawancara. Adapun variabel yang diteliti adalah variabel dependen (kejadian anemia) maupun variabel independen (pengetahuan dan usia kehamilan). Penelitian menunjukkan responden dengan kejadian anemia yaitu 7 (23,3%) dan responden tidak anemia yaitu 23 (76,7%). Responden dengan pengetahuan tinggi yaitu 11 (36,7%) dan responden dengan pengetahuan rendah yaitu 19 (63,3%). Responden dengan usia kehamilan trimester I yaitu 12 (40%), responden dengan usia kehamilan trimester 2 yaitu 8 (26,7%) dan responden dengan usia kehamilan trimester 3 yaitu 10 (33,3%). Hasil analisis chi-square (X2) antara variabel dependen dengan independen menunjukkan ada hubungan bermakna antara pengetahuan dengan kejadian anemia, dengan p value = 0.021< 0,05, dan ada hubungan bermakna antara usia kehamilan dengan kejadian anemia, dimana p value = 0.009 < 0,05, di Puskesmas Talang Ratu Palembang. Diharapkan dapat menjadi masukan bagi tenaga kesehatan khususnya bidan di Puskesmas Talang Ratu Palembang untuk memberikan penyuluhan tentang kejadian anemia..